Gut Microbial Diversity and Genus-level Differences Identified in Cervical Cancer Patients versus Healthy Controls - Sims, Travis T. (Gynecol Oncol, 2019)
OBJECTIVES: The aim of this study was to characterize variation in the gut microbiome of women with locally advanced cervical cancer and compare it to healthy controls. METHODS: We characterized the 16S rDNA fecal microbiome in 42 cervical cancer patients and 46 healthy female controls. Shannon diversity index (SDI) was used to evaluate alpha (within sample) diversity. Beta (between sample) diversity was examined using principle coordinate analysis (PCoA) of unweighted Unifrac distances. Relative abundance of microbial taxa was compared between samples using Linear Discriminant Analysis Effect Size (LEfSe). RESULTS: Within cervical cancer patients, bacterial alpha diversity was positively correlated with age (p = 0.22) but exhibited an inverse relationship in control subjects (p < 0.01). Alpha diversity was significantly higher in cervical cancer patients as compared to controls (p < 0.05), though stratification by age suggested this relationship was restricted to older women (>50 years; p < 0.01). Beta diversity (unweighted Unifrac; p < 0.01) also significantly differed between cervical cancer patients and controls. Based on age- and race-adjusted LEfSe analysis, multiple taxa significantly differed between cervical cancer patients and controls. Prevotella, Porphyromonas, and Dialister were significantly enriched in cervical cancer patients, while Bacteroides, Alistipes and members of the Lachnospiracea family were significantly enriched in healthy subjects. CONCLUSION: Our study suggests differences in gut microbiota diversity and composition between cervical cancer patients and controls. Associations within the gut microbiome by age may reflect etiologic/clinical differences. These findings provide rationale for further study of the gut microbiome in cervical cancer.